The Causes of Naming and the Parts of Clarification in Ibn Al- Atheer’s Book Al-Nihaya fi Gharib Al-Hadith wa Al-Athar - Ahmed, Fadel Abd; Tawfiq Ali, Maha Jassim (Journal of Tikrit University for Humanities, 2023)
The book Al-Nihaya fi Gharib Al-Hadith wa Al-Athar by Imam Ibn Al-Atheer Al-Jazari is one of the most important works of the sixth century AH, which contributed to the service of the Arabic language in general, and the noble hadith in particular. To clarify a large number of strange words, justify their name, and understand the reasons for the names for which they are used, and by which the words multiply, and take different meanings. Scholars have drawn attention to the reasons for which this naming was given to this name and not others. The present paper includes three sections. In the first section the explanation of the naming and its relation to the metaphor. In the second section, the explanation of the naming and its relation to metaphor, and in the third section: the explanation of the naming and its relation to the metonymy Therefore, by explanation the nomenclature and dividing the statement. It is not strange in the well-known sense, but it is strange because of its lack of use, and its difference according to the difference in its pronunciation, because most of the hadiths were narrated with the meaning due to the mixing of the language of the Arabs with the language of non-Arabs at the advent of Islam.